Geometric Stoichiometry: Unifying Concepts of Animal Nutrition to Understand How Protein-Rich Diets Can Be “Too Much of a Good Thing” - Anderson, Thomas R.; Raubenheimer, David; Hessen, Dag O.; Jensen, Kim; Gentleman, Wendy C.; Mayor, Daniel J. (Frontiers in Ecology and Evolution, 2020)
Understanding the factors that control the growth of heterotrophic organisms is central to predicting food web interactions and biogeochemical cycling within ecosystems. We present a new framework, Geometric Stoichiometry (GS), that unifies the disciplines of Nutritional Geometry (NG) and Ecological Stoichiometry (ES) by extending the equations of ES to incorporate core NG concepts, including macromolecules as currencies and the ability of animals to select foods that balance deficits and excesses of nutrients. The resulting model is used to investigate regulation of consumer growth by dietary protein:carbohydrate ratio. Growth on protein-poor diets is limited by nitrogen. Likewise, we show that growth is also diminished on protein-rich diets and that this can be mechanistically explained by means of a metabolic penalty that arises when animals use protein for energy generation. These penalties, which are incurred when dealing with the costs of producing and excreting toxic nitrogenous waste, have not hitherto been represented in standard ES theory. In order to incorporate GS within ecosystem and biogeochemical models, a new generation of integrated theoretical and experimental studies based on unified concepts of NG and ES is needed, including measurements of food selection, biomass, growth and associated physiology, and involving metabolic penalties.